A comparison of coal mine reclamation seed mixes in Kentucky: implications for grassland establishment in Appalachia. Issue 3 (3rd May 2016) - Yeiser, John M.; Baxley, Danna L.; Robinson, Ben A.; Morgan, John J.; Stewart, Jacob N.; Barnard, James O.
Abstract : With approximately 450, 000 hectares of mine land pending reclamation, surface coal mines present an opportunity for large-scale grassland establishment to benefit wildlife. Herein, an alternative reclamation technique is presented that encourages a transition from typical reclamation to wildlife-friendly reclamation. Efficacy of typical, wildlife-friendly and hybrid seed mixes was compared and results indicate that wildlife-friendly mixes met vegetative cover requirements for reclamation in Kentucky. Results demonstrate that alternative methods to typical reclamation have potential to establish large areas of grassland habitat in Appalachian coal regions. Partnerships among mining companies, oversight entities and resource managers are needed to facilitate a transition to wildlife-friendly reclamation.